Studies of pulse waveforms for UWB communications - ZHAO Jun-xi (Tongxin xuebao)
The problem of designing pulse waveforms for UWB communications was investigated.A method of constructing pulse waveforms was proposed by optimally combining different Gaussian functions,and a simple pulse waveform with some desired properties was constructed by the method.Based on the ideal of filtering,a new approach to designing more flexible pulse waveforms for UWB communications was presented.Several numerical experiments were given to demonstrate the efficiency of this method.